The impact of the women's health initiative study on the initiation and continuation of hormone therapy in a tertiary menopause unit in Turkey - (:unkn) unknown (My University, 2007)
Objective: To determine the initiation and continuation rate of hormone therapy (HT) following publication of the Women's Health Initiative (WHI) study. Methods: A survey was performed on 816 postmenopausal women between July 2002 and July 2005. Questions included sociodemographic characteristics, determinants of HT, use of knowledge and source of information regarding the WHI study. Results: The average age was 49,3±3,6 years. Among the participants 22,1% were using HT whereas 77,9% were not . Of the women; 131, 99, 60, 157 were graduated from university, high school, middle and primary school respectively. HT usage was 25% among primary school and 20% among university graduates, which appeared not to be affected by educational level. The rate of starting HT was 18,6% in the second half of 2002. Initiation of HT was 30,5% in 2003, than decreased to 21,5% in 2004 and 20,9% in 2005. Among women for whom HT was initiated after WHI, the continuation rate was 41%. Conclusion: Our survey showed the negative impact of WHI findings on both about the initiation and continuation of HT in our menopause unit in Turkey. Information was mainly obtained through the media or physician, may well have an important impact on the continuation or discontinuation of HT.
Keywords: Hormone treatment; Menopause; WHI